2019
DOI: 10.1073/pnas.1821292116
|View full text |Cite
|
Sign up to set email alerts
|

An ammonite trapped in Burmese amber

Abstract: Amber is fossilized tree resin, and inclusions usually comprise terrestrial and, rarely, aquatic organisms. Marine fossils are extremely rare in Cretaceous and Cenozoic ambers. Here, we report a record of an ammonite with marine gastropods, intertidal isopods, and diverse terrestrial arthropods as syninclusions in mid-Cretaceous Burmese amber. We used X-ray–microcomputed tomography (CT) to obtain high-resolution 3D images of the ammonite, including its sutures, which are diagnostically important for ammonites.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 282 publications
(128 citation statements)
references
References 39 publications
6
105
0
Order By: Relevance
“…findings of marine and freshwater fossils in Myanmar amber, which suggests that the local resinous forest was present adjacent to a coastal embayment or a deltaic environment (Schmidt et al, 2018;Xing et al, 2018;Yu et al, 2019). The hydrophyte niche occupied by Nymphaeaceae extended deep into the Early Cretaceous (Friis et al, 2011) and probably included attractants such as petaloid floral structures with embedded nectar, emission of fruity odors, and receptacular thermogenesis that sequester pollinating insects (Seymour and Matthews, 2006).…”
Section: History and Biology Of Nympheaceaementioning
confidence: 99%
“…findings of marine and freshwater fossils in Myanmar amber, which suggests that the local resinous forest was present adjacent to a coastal embayment or a deltaic environment (Schmidt et al, 2018;Xing et al, 2018;Yu et al, 2019). The hydrophyte niche occupied by Nymphaeaceae extended deep into the Early Cretaceous (Friis et al, 2011) and probably included attractants such as petaloid floral structures with embedded nectar, emission of fruity odors, and receptacular thermogenesis that sequester pollinating insects (Seymour and Matthews, 2006).…”
Section: History and Biology Of Nympheaceaementioning
confidence: 99%
“…atrickmuelleri'. Type stratum and corresponding age: unknown stratum, 98.8 million years, lowermost Cenomanian, lowermost Upper Cretaceous, after Shi et al (2012), stratigraphically supported by a recent record of an ammonite shell of Puzosia (Bhimaites) in Burmese amber (Yu et al, 2019).…”
Section: Systematic Interpretation: Summarymentioning
confidence: 82%
“…In fact, aquatic larvae of Megaloptera (Sialidae) and Neuroptera (Nevrorthidae; Sisyridae) have been found preserved in amber (Wichard, Gröhn & Seredszus, 2009). In recent years, numerous animals which would be considered unlikely to be preserved in fossiliferous resins, such as non-avian forms of Dinosauria and birds (Xing et al, 2016) and an ammonite shell (Yu et al, 2019) have been found. In summary, we cannot really narrow down how the fossil larva might have lived, though aquatic habitats do present an attractive possibility.…”
Section: Possible Life Habits Of the Fossil Larvamentioning
confidence: 99%
“…An ammonite shell preserved in Burmese amber argues that the Burmese amber forest was located near a dynamic and shifting coastal environment ( Yu et al, 2019 ), a conclusion supported by the occurrence of a marine myodocopan ostracod ( Xing et al, 2018 ). Also, semi-aquatic and aquatic insects occur in Burmese amber, including Ochteridae (Hemiptera), Heteroceridae (Coleoptera), Chresmododea and Gerridae (Hemiptera), Dytiscidae and Gyrinidae (Coleoptera), adults and larvae of Odonata, larvae of Psephenidae, Trichoptera, and Ephemeroptera ( Zhang, 2017 ; Xing et al, 2018 ; Schädel, Müller & Haug, 2020 ).…”
Section: Discussionmentioning
confidence: 98%